Agglomeration of iron oxide nanoparticles: pH effect is stronger than amino acid acidity - Godymchuk, Anna Yu; Papina, Iuliia; Karepina, Elizaveta; Kuznetsov, Denis; Lapin, Ivan N.; Svetlichnyi, Valerii A. (Journal of Nanoparticle Research)
Wet methods for nanoparticle characterization need to use the surfactants to prevent the agglomeration of particles in hydrosols. In this work, we investigated the effect of pH on the agglomeration state and the stability of differently sized Fe2O3 nanoparticles, notably 35 and 120 nm in average, in amino acid solutions as glycine, l-lysine and l-glutamine, using the method of dynamic light scattering. The lowest electrokinetic stability and maximum agglomeration of both hydrosols was found in the acidic medium, particularly, at pH = 3.5 for Fe2O3-35 and pH = 6.5 for Fe2O3-120 (surface isoelectric point). At pH ≤ 7 in amino acid-based solutions, the charge direction was depended on the particles size. The pH growth from 5 to 9 suppressed Fe2O3 particle agglomeration although the effect of pH was much higher in glycine (neutral amino acid) where the agglomerates' size decreased by 4.5 times compared with 2.8 in glutamine (acidic amino acid) and 1.8 in lysine (basic amino acid). It was concluded that the pH predominantly affected an agglomeration with respect to the particle size and acidity of amino acids. In alkali medium at pH = 9, particles had a maximum charge and minimum size in all solutions. For example, in glycine, the average size/zeta potential of Fe2O3-35 and Fe2O3-120 agglomerates were, respectively, 180 ± 20 nm/− 32 mV and 263 ± 80 nm/− 38 mV compared with water 510 ± 20 nm/− 18 mV and 180 ± 69 nm/− 24 mV. © 2019, Springer Nature B.V.